Pengaruh Lingkungan Terhadap Perkembangan Bahasa Anak Usia Dini - Nurainun Nurainun; Mayana Futri (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
The role of the environment is a forum in the process of developing children's language and speech skills, because the environment is part of the child's interactions in the development process. The aim of this research is to describe the role of the environment in children's language development. The method in this research uses a qualitative method with a literature approach or literature study. Sources taken from various kinds of literature, including journals, articles and previous research as well as other internet sources. The results of this study show that the role of the environment is very important in language development, because language in early childhood can develop or not depending on the stimulus provided by the environment around the child, whether in the family environment, school environment, or living environment or community.